Establishment of a monitoring network for potato late blight (Phytophthora infestans) in Poland - Kapsa, Józefa; Hansen, Jens G. (Plant Breeding and Seed Science, 2004)
Changes in population of Phytophthora infestans can greatly influence the time of potato late blight appearance in potato crops. The late blight monitoring system makes it possible to evaluate reliability of the forecast provided by decision support systems that are applied in potato protection and in consequences defends in practice potato crops from early appearing infections. The first steps in creating Polish internet monitoring system in potato protection against late blight were based on observations carried out by advisers from the Plant Protection Inspectorate in Lublin voivodeship in the years 2001-2002. The conducted evaluations were part of the Polish-Danish research project “Development of an Internet based DDS for Cereal Diseases and Potato Late Blight in Poland, 2001-2002”. In 2003, the observations were also conducted in four other voivodeships. The collected results indicate that it is feasible to recognize primary early infections manifested as singular necroses on potato plants. The earliest infections were most frequently recorded on susceptible potato cultivars. In two cases in 2003, early attacks were recorded at plant growth stage of 30-31 (in 0-99 BBCH scale for potato). In most cases the first infection symptoms appeared at the growth stage exceeding 37. This indicates that very early infections caused by oospores from soil were not common in the inspected areas.